What is important for the growth of latecomers in the medical device industry? - Kyungtae Yeom; Changhyeon Song; Kwangsoo Shin; Ho Seon Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
In the medical device industry, which is highly value-added and requires multidisciplinary knowledge, major global firms dominate the market, so it is necessary to establish a growth strategy suitable for latecomers. Through a Korean case, it was confirmed that import, diversification, and R&D activity are distinguishing strategies. The existing literature covers these strategies, but these findings are fragmented and differ from those of latecomers. This study examined the impact of the above factors on corporate growth, based on data of 440 Korean medical device manufacturers from 2011 to 2016. According to the results of panel data regression, diversification and R&D activity have a positive effect on the financial performance of a firm, while the import business model shows a negative effect. These results are expected to provide implications with respect to strategies for the growth of latecomers in the medical device industry. In future research, it is necessary to investigate how detailed strategies in accordance with the growth stages of a firm can be established.
Keywords: 650; D activity; diversification; import business model; latecomer; medical device industry; R&amp